Investigating the impact of non-nutritive sweeteners on the antifungal potential of alcoholic and aqueous Eucalyptus extracts against salivary candida albicans (An in-vitro study) - AL-Qaralusi , Dalya M.; Al-Mizraqchi , Abbas S (Journal of Baghdad College of Dentistry, 2023)
Background: Eucalyptus extracts and derivatives are natural substances with potent antimicrobial properties. This study investigated the in- vitro effects of non-nutritive sweeteners on the antifungal activity of alcoholic and aqueous Eucalyptus extracts against Candida albicans, a common oral pathogen. Materials and Method: Ten isolates of Candida albicans were isolated from dental students’ salivary samples. The alcoholic and aqueous extracts were prepared from fresh Eucalyptus leaves using maceration. The sensitivity of Candida albicans isolates to various concentrations of Eucalyptus extracts ranging from 50 to 250 (mg/mL) was evaluated via agar well diffusion method, while the agar streaking method  was used to assess the minimum fungicidal concentration (MFC). In addition, the effect of non-nutritive sweeteners on the MFC of the extracts was investigated. Results: The Eucalyptus extract-sensitive Candida albicans isolates showed an increase in inhibitory zone width with increasing extract concentration. Regarding their antifungal effectiveness, clear disparities were observed among extract concentrations. Against Candida albicans, the MFC for Eucalyptus alcoholic extract was 75 mg/mL, but the MFC for Eucalyptus aqueous extract was 200 mg/mL. Notably, 15% stevia and 5% sucralose did not affect the antifungal effects of the Eucalyptus alcoholic extract. The antifungal effectiveness of the aqueous Eucalyptus extract against Candida albicans was unaffected by stevia and sucralose concentrations of up to 1%. Conclusion: Significant antimicrobial action against Candida albicans is shown in Eucalyptus extracts. Results indicated that stevia and sucralose at specific quantities could be utilized as sweeteners for Eucalyptus extracts in an efficient manner without impairing the extracts’ antifungal activity.